Gd(OH)3 as Modifier of Iron Oxide Nanoparticles—Insights on the Synthesis, Characterization and Stability - María Gabriela Montiel Schneider; Paula Sofía Rivero; Guillermo Arturo Muñoz Medina; Francisco H. Sanchez; Verónica Leticia Lassalle (Colloids and Interfaces, 2023)
Magnetic resonance imaging is one of the most widely used diagnostic techniques, since it is non-invasive and provides high spatial resolution. Contrast agents (CAs) are usually required to improve the contrast capability. CAs can be classified as T1 (or positive) or T2 (or negative) contrast agents. Nowadays, gadolinium chelates (which generate T1 contrast) are the most used in clinical settings. However, the use of these chelates presents some drawbacks associated with their toxicity. Iron oxide magnetic nanoparticles (MNPs) have been extensively investigated as CA for MRI, especially for their capacity to generate negative contrast. The need for more efficient and safer contrast agents has focused investigations on the development of dual CAs, i.e., CAs that can generate both positive and negative contrast with a single administration. In this sense, nanotechnology appears as an attractive tool to achieve this goal. Nanoparticles can be modified not only to improve the contrast ability of the current CAs but also to enhance their biocompatibility, resolving toxicity issues. With the aim of contributing to the field of development of dual T1/T2 contrast agents for MRI, here, we present the obtained results of the synthesis of hybrid nanoparticles composed of magnetite/maghemite and gadolinium hydroxide. Exhaustive characterization work was conducted in order to understand how the hybrid nanoparticles were formed. The nanoparticles were extensively characterized through FTIR and UV–Vis spectroscopy, TEM and SEM microscopy, X-ray diffraction (XRD) analysis, dynamic light scattering, zeta potential, thermogravimetric analysis, energy-dispersive X-ray and vibrating-sample magnetometry. Stabilization studies were carried out to get an idea of the behavior of nanohybrids in physiological media. Special interest was given to the evaluation of Gd3+ leaching. It was found that carbohydrate coating as well as the adsorption of proteins on the surface may improve the stabilization of hybrid nanoparticles.